Innovating for the middle of the pyramid in emerging countries - Cuervo-Cazurra, Alvaro 1968-; Montoya, Miguel A. (Cambridge University Press, 2021)
The transformation of emerging markets in recent decades has generated a new, growing, and very large middle class market, also known as the middle of the pyramid. This market segment, which is middle by the standards of emerging markets yet low by the standards of advanced economies, is extremely attractive for firms, but still understood and underserved. This volume presents detailed analyses of exemplary firms that have innovated products, services, and business models to fulfil the needs and desires of these new middle classes. It provides useful insights for managers, consultants, researchers, and students interested in emerging economies, and actionable lessons on how to innovate for a new and expanding market segment